Study guides

☆☆

Q: How do you simplifying algebraic -2a 6a?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is two terms of an algebraic expression in the form of 6a-8

2a+3a=5a

Only like terms can be subtracted or added in algebraic expressions.

There are a few rules for simplifying an algebraic expression. Specifically, one should combine like terms, and then they should try to isolate the variable by doing the opposite, either multiplication or division.

322

Related questions

Since the question is 3(2a), then just write it out. 3(2a) is 2a+2a+2a or 6a.

2a-6a+9-4a+9

6a

6a to the second power minus 8ab + 2a

6a2

5a-20+2a = 6a-11 5a+2a-6a = 20-11 1a = 9 a = 9

I guess you mean: 2a^2+6a Well in this case you take 2a out of the bracket and then you're left with a+3 inside. 2a(a+3a)

6a squared-8ab+2a factor completely and check mentally

The value of a in the equation 5a plus 2a = 6-6a is a=6/11.

12a²

-4 + 10 + 6a - 2a + 3 9 + 4a

2a+2b+3a+3b+a+b= 6a+6b 2a+3a+a=6a 2b+3b+b=6b

People also asked